ASSOCIATION OF ABNORMAL UTERINE BLEEDING WITH BODY MASS INDEX AMONG WOMEN ATTENDING GYNAECOLOGY OUTPATIENT DEPARTMENT, PURNEA, BIHAR. - Nikhat Fatma (Student's Journal of Health Research Africa, 2024)
Background Abnormal uterine bleeding (AUB) is a general gynecological condition that significantly affects women’s health and quality of life. Body mass index (BMI) is a well-established factor influencing reproductive health, and its impact on AUB has been observed but not extensively studied in low-resource settings. This study aims to examine the association between BMI and AUB among women attending the gynecology OPD. Methods A total of 144 women were included based on specific inclusion and exclusion criteria. Data were collected on socio-demographic parameters, menstrual history, obstetric history, and BMI. BMI was calculated and categorized according to the World Health Organization (WHO) classification. The prevalence of AUB was determined across different BMI categories, and statistical analysis was accomplished using SPSS version 23.0. Results The study found that 54.9% of participants had AUB. Obese women had the highest incidence of AUB (73.7% in obese class I and 100% in obese class II and III), with a substantial relationship between higher BMI and increased AUB prevalence (p < 0.05). Obesity was also associated with higher rates of ovulatory dysfunction (32.4%) and iatrogenic causes of AUB. The prevalence of heavy menstrual bleeding and irregular periods was notably higher in women with higher BMI categories. Conclusion There is a significant association between higher BMI and increased incidence of AUB among women attending the gynecology OPD. These findings suggest that obesity is a critical factor contributing to menstrual irregularities and AUB, underscoring the need for targeted interventions in this population. Recommendations Comprehensive AUB care should include BMI testing in routine gynecological exams and weight management counseling. More study is needed to understand the processes between BMI and AUB and create customized therapies for obesity-related menstrual problems.